(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
To determine the impact of ski tourism on the psycho-emotional state of students, a color matrix was created that reflected emotions before and after classes in the snowy period of the second academic semester. The pedagogical experiment was conducted at the Yuriy Fedkovych Chernivtsi National University with the participation of students of 3rd and 4th courses of the Faculty of Physical Culture, Sports and Rehabilitation. There were 42 people and were divided into two groups of 21 male students. The color diagnostic method is a psychological method for assessing the emotional state and interpersonal relationships based on color preferences. It is used in pedagogy, psychology and the social sphere to diagnose mood, anxiety level and psychological comfort of a person. color diagnostic method for studying the psycho-emotional state of students and their adaptation to the educational process. Its approach is based on the analysis of color associations as indicators of the internal state of the individual. Psycho-emotional states remain positive in response to new, unusual or complex situations and activities, performing an adaptive function in relation to unfamiliar places, routes, environment, conditions, mood. Ski tourism is part of the state system of physical culture and sports, aimed at developing physical, intellectual and volitional qualities through hiking and competitions. It contributes to increasing labor and social activity, satisfying the creative and aesthetic needs of people. Frosty air and picturesque winter landscapes relieve fatigue and stress, fill with energy and give a good mood for the entire academic and working week. The use of the color diagnostics method showed that the use of ski tourism in the educational and training process of students has a positive effect on their psycho-emotional state. The purpose of the study: to theoretically substantiate and experimentally verify the influence of ski tourism on the psycho-emotional state of students of various specialties.